The Parental involvement in academic affairs of children with vision impairment enrolled at primary level in government special education institutions of Punjab: An evaluative investigation - Jahanzaib, Muhammad; Fatima, Ghulam (South Asian Review of Business and Administrative Studies (SABAS), 2023)
The purpose of this research was to determine the kind and degree of parental engagement in the primary level CWVI’s education provided by government special education organizations in Punjab, Pakistan. Mixed-method descriptive study was conducted. 53 fifth-grade kids with visual impairment, 31 randomly chosen parents, and 127 special education teachers (JSETs and SSETs) were the sample of study. Multistage sampling approaches were used to collect data. Teachers and CWVI individually completed the surveys for the researcher. While all parent interviews were conducted over the phone with the permission of school administration. The five experts on the panel verified each of the three research tools. Chronbech alpha was used to assess the accuracy of questionnaires, and the results are as follows.840 for the teacher survey and.792 for the survey on children with visual impairment. Quantitative data was analyzed using descriptive and inferential statistics, while qualitative data was analyzed using theme analysis. According to the study, parents cannot provide their CWVI the assistance they need since the majority of them have poor socioeconomic and educational status. Similar to a lot of instructors believed that parents did not provide their kids with visual impairment same opportunity as they did for their other children, however CWVI refuted this notion. According to the study, individualized family assistance plans should be implemented to help care takers of CWVI. Additionally, training programmes on teaching Braille literacy, arithmetic, the operating the helping aids, etc. Maybe offered to parents of CWVI. Key words; Children with vision impairment, academic affairs, level of parental involvements